Farm Forestry in Agricultural Southern Ontario, ca. 1850-1940: Evolving Strategies in the Management and Conservation of Forests, Soils and Water on Private Lands - Bowley, Patricia (Scientia Canadensis, 2015)
Early settlers in southern Ontario aspired to become prosperous land-owning farmers; they began by cutting trees. Within a few decades, wind and water, unimpeded by forest cover, devastated soil and crops. Farmers were encouraged by groups such as the Ontario Fruit Growers’ Association to reforest some of their land. Farm forestry, as part of scientific agriculture, had a strong beginning in the early 1900s with the Ontario Agricultural and Experimental Union, but that movement was poorly supported until the 1930s, when the relationship between deforestation and water supplies reached a crisis. The Ontario Conservation and Reforestation Association (OCRA) and the Ontario Crop Improvement Association (OCIA) were created in agricultural southern Ontario in 1937-8 after a disastrously hot dry summer. Each organization interpreted the conservation of natural resources in profoundly different ways: the OCRA as a movement to create forest resources on public property, and the OCIA as management of privately-owned farmlands to improve crop production.